2020
DOI: 10.3389/fnhum.2020.589802
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory in Aphasia: The Role of Temporal Information Processing

Abstract: Aphasia is an acquired impairment of language functions resulting from a brain lesion. It is usually accompanied by deficits in non-linguistic cognitive processes. This study aimed to investigate in patients with aphasia the complex interrelationships between selected cognitive functions: auditory speech comprehension, working memory (WM), and temporal information processing (TIP) in the millisecond time range. Thirty right-handed subjects (20 males) aged from 27 to 82 years suffering from post-stroke aphasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Murray (2012) argued that different patterns of performance could be associated with different aphasia types, as her findings showed that only individuals with anomic aphasia presented relatively spared attention measured through the Test of Everyday Attention (Robertson et al, 1994), whereas variables like age, education or aphasia severity did not have any effect on performance. Laures-Gore et al (2011), on the other hand, found a significant association between severity of aphasia and working memory measures, as well as Choinski et al (2020). In summary, even though there is wide evidence that individuals with aphasia tend to present nonverbal cognitive deficits, it is still unclear to what extent and what causes them, and whether they are directly correlated or not with their linguistic deficits.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Murray (2012) argued that different patterns of performance could be associated with different aphasia types, as her findings showed that only individuals with anomic aphasia presented relatively spared attention measured through the Test of Everyday Attention (Robertson et al, 1994), whereas variables like age, education or aphasia severity did not have any effect on performance. Laures-Gore et al (2011), on the other hand, found a significant association between severity of aphasia and working memory measures, as well as Choinski et al (2020). In summary, even though there is wide evidence that individuals with aphasia tend to present nonverbal cognitive deficits, it is still unclear to what extent and what causes them, and whether they are directly correlated or not with their linguistic deficits.…”
Section: Introductionmentioning
confidence: 94%
“…The studies on the relationship between specific nonverbal and verbal cognitive skills in individuals with aphasia are also inconclusive. While some studies have reported significant associations between linguistic and nonverbal cognitive tasks (Fucetola et al, 2009;Murray, 2012;Lee and Pyun, 2014;Marinelli et al, 2017;Wall et al, 2017;Choinski et al, 2020), others have not found any significant relationship between them (van Mourik et al, 1992;Helm-Estabrooks, 2002;Ivanova et al, 2017;Little et al, 2019). Also, most of the studies observed a great variability among individuals with aphasia in nonverbal cognitive measures which, as some have already argued (Murray, 2012;Marinelli et al, 2017), suggests that cognitive deficits alone cannot explain the linguistic impairments in aphasia.…”
Section: Introductionmentioning
confidence: 97%
“…Time may be considered as the frontier in cognitive sciences and a fundamental property of working human brains. Much evidence from both everyday observations and extensive research studies has consistently indicated that many cognitive functions-such as language, perception, short-term and working memory, attention, motor activity, decision making, executive functions, etc.,-are temporally segmented in specific time intervals and are rooted in a defined temporal template (e.g., Szelag et al, 2004aSzelag et al, , 2008Szelag et al, , 2010Szelag et al, , 2011Szelag et al, , 2014Szymaszek et al, 2009Szymaszek et al, , 2018Ulbrich et al, 2009;Oron et al, 2015;Nowak et al, 2016;Buhusi et al, 2018;Szelag, 2018;Choinski et al, 2020;Jablonska et al, 2020). Temporal information processing (TIP) is omnipresent, for example in every verbal or perceptual act, in movement control, in learning, and in planning.…”
Section: Introduction Temporal Constraints Of Cognitive Functionsmentioning
confidence: 99%
“…When the order of two sounds is judged, the two stimuli must differ by at least one dimension to enable identification. As a result, auditory TOJ paradigms use stimuli that differ either in: a) frequency (pitch) [ 1 14 ]; or b) spectrum (pure tone vs. noise) [ 14 ]; or c) duration [ 14 , 15 ]; or d) the ear of presentation, i.e., the ear that receives the first and the ear that receives the second stimulus (referred to as dichotic, spatial, or binaural TOJ) [ 1 3 , 5 – 12 , 14 , 16 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hirsh and Sherrick [ 27 ] originally reported the threshold for TOJ to be 17 msec, regardless of the type of stimulus and presentation modality used [ 27 ]. However, more recent studies have, generally, reported longer thresholds [ 1 3 , 5 – 7 , 10 12 , 14 , 16 17 , 20 , 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%